Betacellulin (BTC) Biases the EGFR To Dimerize with ErbB3 - Rush, Jamie S. (Mol Pharmacol, 2018)
There are 13 known endogenous ligands for the epidermal growth factor receptor (EGFR) and its closely related ErbB receptor family members. We previously reported that betacellulin (BTC) is more efficacious than epidermal growth factor (EGF) in mediating corneal wound healing, although the molecular basis for this difference was unknown. For the most part, differences between ligands can be attributed to variability in binding properties, such as the unique rate of association and dissociation, pH sensitivity, and selective binding to individual ErbB family members of each ligand. However, this was not the case for BTC. Despite being better at promoting wound healing via enhanced cell migration, BTC has reduced receptor affinity and weaker induction of EGFR phosphorylation. These data indicate that the response of BTC is not due to enhanced affinity or kinase activity. Receptor phosphorylation and proximity ligation assays indicate that BTC treatment significantly increases ErbB3 phosphorylation and EGFR-ErbB3 heterodimers when compared with EGF treatment. We observed that EGFR-ErbB3 heterodimers contribute to cell migration, because the addition of an ErbB3 antagonist (MM-121) or RNA interference–mediated knockdown of ErbB3 attenuates BTC-stimulated cell migration compared with EGF. Thus, we demonstrate that, despite both ligands binding to the EGFR, BTC biases the EGFR to dimerize with ErbB3 to regulate the biologic response.